The African Elephant Database - Douglas-Hamilton, Iain (Pachyderm, 1993)
Outlines the background and development of the African Elephant Database and notes aspects associated with variation in data quality. Suggests that the variability if data quality does not negate the value of the database in population monitoring nor in its use in trend analysis and notes that it is important the AfESG work towards making the data collection better and enhancing its analysis.